(In)Sucesso da Marcação CE nos Dispositivos Médicos. Análise SWOT e Propostas de Melhoria (Maria Judite Neves, Hélder Mota Filipe) - Maria Judite Neves; Hélder Mota Filipe (Formifarma, LDA., 2012)
Although the regulatory framework which is applied to medical devices is, by itself, adequate and able to guarantee the quality, safety and correct performance of medical devices, improving its application implies a great commitment from all parts involved in the device's life cycle and a proper implementation of all legislative measures available. However, the sector has a dynamic and evolutionary characteristic of its own, forcing a continual reflection in the context of its continuous improvement. At the present, the European Commission proposes to revise the current legislative framework, recognizing that Europe needs to evolve to a more intelligent system that enables the effective and efficient management of existing resources, requires the committed involvement of all stakeholders, ensures simplicity and flexibility in regards to innovation, and which simultaneously ensures appropriate security levels, and promotes greater public confidence in the regulatory system. This article seeks to present the current regulatory framework for medical devices, the responsibilities of stakeholders, as well as key issues, and proposals for improvement discussed in the legislative revision process. In this context, a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) on the regulatory system for medical devices, is presented.